2021
DOI: 10.1038/s41598-021-00397-1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal, liver and lipid disorders in genetically obese rats are more efficiently reduced by dietary milk thistle seeds than their oil

Abstract: We hypothesized that milk thistle seed or seed oil dietary supplementation reduces intestinal, liver and lipid disorders specific to genetic obesity, and the seeds can be more efficient in doing so. Lean and obese male Zucker rats were allocated to 4 groups: the lean (LC) and obese control (OC) groups fed a standard diet and the other 2 obese groups fed a diet supplemented with milk thistle seed oil (O + MTO) or milk thistle seeds (O + MTS). After 5 weeks of feeding, the cecal SCFA pool was slightly and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…SCFAs, mainly acetate, propionate and butyrate, are the major end products of dietary fibre fermentation in the distal intestine, and they are considered indirect nutrients for the body [ 29 ]. Interestingly, milk thistle fibre was well fermented to propionate at the expense of acetate, which confirmed previous findings of increased propionate production from milk thistle fibre in the distal gut of genetically obese rats [ 23 ]. Propionate fermentation is especially important, because after absorption into the bloodstream, this acid reaches the liver, thus decreasing lipogenesis [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…SCFAs, mainly acetate, propionate and butyrate, are the major end products of dietary fibre fermentation in the distal intestine, and they are considered indirect nutrients for the body [ 29 ]. Interestingly, milk thistle fibre was well fermented to propionate at the expense of acetate, which confirmed previous findings of increased propionate production from milk thistle fibre in the distal gut of genetically obese rats [ 23 ]. Propionate fermentation is especially important, because after absorption into the bloodstream, this acid reaches the liver, thus decreasing lipogenesis [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…MTSs also contained a considerable amount of fat (25%), whereas PMSs had significantly less fat (10%). Additional details on the chemical composition of MTSs used in the present study have been previously reported [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oleic acid), phytosterols, alpha tocopherol, quercitin, histamine, tannins, minerals and vitamins. 2,7,18,26…”
Section: Substances Contained In Milk Thistlementioning
confidence: 99%
“…Opyd and Jurgoński (2021) studied the impact of MSTO supplementation on liver disorders in genetically obese rats [7].…”
Section: Introductionmentioning
confidence: 99%